Revisiting the Weak Form Efficiency with Structural Breaks: Evidence from the Indian Stock Market - Parthasarathy, Srikanth (Indian Journal of Finance, 2019)
This study investigated the weak form efficiency in the Indian stock market after accounting for structural breaks. The parametric and non-parametric Wright (2000) sign variance ratio test and its multiple variance ratio extensions, after accounting for structural breaks based on Bai and Perron (2003), were used in this study. This study found that the large, middle, and small capitalization indices were not weak form efficient based on the variance ratio tests on daily data for the 2000-2017 period. However, once the structural breaks were accounted for, this study found the large capitalization indices to be weak form efficient. However, the middle and small capitalization indices were not weak form efficient, even after accounting for structural breaks. The notion of adaptive or evolving market efficiency was also supported in this study. The traders will not get abnormal economic profits by trading in the large capitalization space. However, outside the large capitalization space, there is potential for abnormal economic profits. This study supports the assertion that if the structural breaks were not considered, weak form of market efficiency tests might give misleading results. The present study is different from most other studies in the Indian market by accounting for the structural breaks in the weak form of efficiency tests.